PMU signal prioritization for effective control coordination of load despatch centres - Pandey R.K.; Archana S.M.; Nayyar K.; Pentayya P.; Kumar C. (My University, 2025)
The power system network operational aspect has been very challenging due to dynamical variations. The energy control centres have the responsibility of maintaining the grid parameters mainly frequency and voltage at each bus in a given network configuration. The usage of SCADA data has been of value till date in making the decision, but in real time, the delay and skewed data sometimes results in imprecise decisions. The new generation synchrophasor technology with PMUs has been visualized by the power utilities of great help in observability of grid parameters variations. However, the integration of PMUs signalling with energy control centres for identifying the events and related automated control decisions have not be adequately addressed. This paper identifies the concept of PMU signal prioritization based on the data mining algorithm and proposes a methodology based on signal selection criterion for initiating the control decision by energy control centres to ensure smooth system operation in real time in the event of some parametric changes such as system loading or change in power injection. The algorithm may be embedded with data concentrators in parallel processing mode with each PMU signal and corresponding output will assist the Grid operational strategy in real time without manual intervention. © 2014 IEEE.